Analysis of The Influence of Socioeconomic Situation and Educational Policy on The Improvement of Education Quality in Indonesia - Lenny Nuraeni; Anugriaty Indah Asmarany; Ichsan Ichsan; Iwan Henri Kusnadi; Sri Subekti (Departement of Mathematics Education, 2024)
The aim of this research is to provide an understanding of the current state of education, with a focus on quality education, equity and equality. Information was obtained from respondents using surveys and questionnaires. The research results show that although public access to education has increased, there has been a decline in academic achievement, this shows the importance of quality in the formulation of education policies. Even though there are still disparities in the quality of education based on socio-economic background, there has been an increase in equal distribution of opportunities to obtain education. To ensure educational equality, it is suggested that it is necessary to increase literacy and expand access to information. The government must also ensure that every child has fair access to the best education, and requires a more comprehensive and long-term education policy.